NMR Study of the Complex Formation in Solution - Zavelsky, V.O.; Kalashnikova, I.P.; Kazachenko, V.P.; Baulin, V.E.; Raevsky, O.A. (Biomedical Chemistry: Research and Methods, 2018)
NMR spectroscopy has been used to study the complexation of organic ligands, that are of interest for biology and medicine, with ions of biologically significant metals (Li+, Na+, Ca2 +, Ga3+). The possibilities and advantages of NMR spectroscopy methods in the study of complex formation are shown. A high sensitivity of the NMR signal to the formation of a complex even with a very small natural concentration of the magnetic isotopes is detected. The formation of a complex with a low stability constanthas has been found by 43Ca NMR spectroscopy. The equilibrium constants of the complexes and the parameters of their NMR spectra are obtained. The possibility of using the 31P and 13C NMR method for initial testing of the complexation of cyclene derivatives with the cation Ga3+ in D2O is shown.